2000
DOI: 10.1161/01.hyp.36.5.813
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear Integrins, Membrane Fluidity, and Cytosolic Ca 2+ Content After Activation in Essential Hypertension

Abstract: Abstract-The purpose of this research was to obtain further information about the role of polymorphonuclear leukocytes in essential hypertension. These cells could be involved in the pathogenesis of organ injury. Thirty subjects (14 men and 16 women) with essential hypertension were enrolled. In these subjects we determined, at baseline and after in vitro activation with 4-phorbol 12-myristate 13-acetate and N-formyl-methionyl-leucyl-phenylalanine, the polymorphonuclear leukocyte membrane fluidity, obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…In addition, it has to be emphasized, while in normal controls and in VAD subjects without DM we found a significant positive correlation between PMN membrane fluidity and PMN cytosolic Ca 2+ concentration, this finding was not observed in the group of VAD subjects with type 2 DM [18]. The same results have been noted in hypertensive [20,21,22] and in CKD patients [23,24,25,26]. At baseline, in subjects with essential hypertension we found an increase in PMN cytosolic calcium content only.…”
Section: Chronic Clinical Conditionssupporting
confidence: 63%
“…In addition, it has to be emphasized, while in normal controls and in VAD subjects without DM we found a significant positive correlation between PMN membrane fluidity and PMN cytosolic Ca 2+ concentration, this finding was not observed in the group of VAD subjects with type 2 DM [18]. The same results have been noted in hypertensive [20,21,22] and in CKD patients [23,24,25,26]. At baseline, in subjects with essential hypertension we found an increase in PMN cytosolic calcium content only.…”
Section: Chronic Clinical Conditionssupporting
confidence: 63%
“…In addition, Dorffel et al [36] have provided evidence for preactivation and enhanced susceptibility of peripheral blood monocytes to angiotensin-II-mediated cytokine generation in humans with essential HTN. Likewise, Caimi et al [37] have demonstrated a significant increase in integrin expression and cytosolic Ca 2+ concentration, as well as enhanced susceptibility to phorbol ester and fMLP-mediated activation in polymorphonuclear leukocytes from humans with essential HTN. Taken together, published studies in animals and humans with genetic HTN have provided compelling evidence for spontaneous activation of circulating leukocytes.…”
Section: Discussionmentioning
confidence: 90%
“…Cellularactivation is generallyreflected in altered intracellularcalcium concentration and membrane fluidity.Calcium acts as asecondmessenger, initiating anumber of pathwaysinvolved in cell migration, adhesion, survivala nd coagulation in cells (20)(21)(22),and free cytosolic calcium providesameasureofcellularactivation. Cellularplasma membrane fluidity (the reciprocal of membrane microviscosity) defines the moleculardynamics of associated receptor proteins that arei nvolved in cell adhesion, migration and coagulation (23)(24)(25).Changesinmembrane fluidity can reflect or parallelaltered calcium homeostasis and cellularcytoskeleton organization. Altered cell activation and potentialc hangesi nc ella dhesion, migration and invasion are expected to change the fluidityinthe coreand surfaceofthe cell membrane (24).…”
Section: Introductionmentioning
confidence: 99%